LIPID PEROXIDATION AND ANTIOXIDANTS IN ALZHEIMER’S DISEASE - SHASHIKANT V. NIKAM; PADMAJA S. NIKAM; S. K. AHALEY (International Journal of Pharma and Bio Sciences, 2010)
The concepts of oxidative stress and antioxidants have been implicated in neurodegenerative disorders. Oxidative stress was assessed by estimating lipid peroxidation product in the form of thiobarbituric acid reactive substances (TBARS). Enzymatic antioxidants like superoxide dismutase(SOD), glutathione peroxidase(GPx), catalase, ceruloplasmin and non enzymatic antioxidant vitamins like vitamin-E, vitamin-C were estimated in either serum or plasma or erythrocyte in 25 patients of Alzheimer’s disease and control subjects in the age group 60-85 years. The trace elements copper, zinc and selenium were also estimated. Plasma lipid peroxidation levels were significantly raised but activity of superoxide dismutase, glutathione peroxidase, catalase, ceruloplasmin and levels of vitamin–E, vitamin-C, copper; zinc and selenium were significantly reduced in Alzheimer’s disease in comparison with control subjects. Study indicates that elevated oxidative stress and reduced antioxidant status may be playing role in cholinergic, noradrenergic and dopaminergic cell loss and involved in pathogenesis of Alzheimer’s disease.